2019
DOI: 10.1002/jcb.29046
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of heme oxygenase‐1 in microenvironment mediates vincristine resistance of B‐cell acute lymphoblastic leukemia by promoting vascular endothelial growth factor secretion

Abstract: Chemoresistance often causes treatment failure of B‐cell acute lymphoblastic leukemia (B‐ALL). However, the mechanism remains unclear at present. Herein, overexpression of heme oxygenase‐1 (HO‐1) was found in the bone marrow stromal cells (BMSCs) from B‐ALL patients developing resistance to vincristine (VCR), a chemotherapeutic agent. Two B‐ALL cell lines Super B15 and CCRF‐SB were cocultured with BMSCs transfected with lentivirus to regulate the expression of HO‐1. Silencing HO‐1 expression in BMSCs increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Our co-expression analysis revealed that LINC00152 regulates genes involved in substrate cellular adhesion processes, one of the main biological mechanisms associated with relapse and chemoresistance in ALL. Chemoresistance has been addressed in several studies as one of the most important mechanisms of relapse and death in ALL [40][41][42]. Taking together, these data and our findings regarding the association between LINC00152 high expression and the high risk of relapse suggest that LINC00152 could be potentially involved in chemoresistance; however, functional studies are required to prove these remarks.…”
Section: Linc00152 and Linc01013 Expression In Acute Lymphoblastic Leukemiasupporting
confidence: 56%
“…Our co-expression analysis revealed that LINC00152 regulates genes involved in substrate cellular adhesion processes, one of the main biological mechanisms associated with relapse and chemoresistance in ALL. Chemoresistance has been addressed in several studies as one of the most important mechanisms of relapse and death in ALL [40][41][42]. Taking together, these data and our findings regarding the association between LINC00152 high expression and the high risk of relapse suggest that LINC00152 could be potentially involved in chemoresistance; however, functional studies are required to prove these remarks.…”
Section: Linc00152 and Linc01013 Expression In Acute Lymphoblastic Leukemiasupporting
confidence: 56%
“…This intercellular communication leads to the secretion of prosurvival cytokines (IL-8) and chemoattractants interferon gamma-induced protein/ CXC chemokine ligand 10 (IP10/CXCL10), monocyte chemotactic protein-1 (MCP-1)/CCL2) enhancing the resistance of leukemic cells to steroids [76]. In addition, via the expression of heme oxygenase-1 and the release of vascular endothelial growth factor (VEGF), MSCs promote resistance to vincristine [77]. MSCs can also protect ALL cells against the treatment by secretion of soluble or stroma-cell-bound galectin-3, which stimulates expression of endogenous LGALS3 mRNA and activates the tonic NF-κB pathway in leukemic cells [78].…”
Section: Growth-supporting and Protective Role Of Mesenchymal Stem Cementioning
confidence: 99%
“…Moreover, VEGF and basic fibroblast growth factor (bFGF) were also detected in urine and peripheral blood samples from ALL patients and correlated with the increase in bone marrow angiogenesis ( 103 ). VEGF can be regulated by signaling pathways such as PI3K/AKT, as demonstrated in B-ALL cell lines and patients, where an overexpression of heme oxygenase-1 (HO-1) was found in the bone marrow stromal cells (BMSCs) ( 104 ). It was found that B-ALL cell lines became resistant to the chemotherapeutic agent vincristine (VCR) in presence of VEGF recombinant protein induced by HO-1 expression.…”
Section: The Role Of Angiogenesis In Allmentioning
confidence: 99%